2020
DOI: 10.29252/ibj.24.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Vitamin C with Cisplatin for Inhibiting Proliferation of Gastric Cancer Cells

Abstract: Background: Ascorbic acid, known as vitamin C, has been used in combination with a number of cytotoxic agents in vitro and in vivo with contradictory results on its effectiveness. It is believed that vitamin C can sensitize different cancer cells to common therapy strategies such as chemotherapy and radiotherapy. During current research, the combination effect of vitamin C with cisplatin was evaluated against gastric cancer cells. Methods: MTT-based proliferation assay, CI method, and flow cytometry technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…More recently, it has been shown that vitamin C at pharmacologic plasma concentrations acquired intravenously can selectively kill the tumor cells but had little cytotoxic effect on normal cells; and these effect was mainly through a reactive oxygen species (ROS) dependent way [ 16 18 ]. These findings have inspired other studies to provide new insights into the function of combining therapy with vitamin C in treating different types of cancers [ 19 21 ]. Nevertheless, the function and the mechanism of combining therapy with vitamin C and PLX4032 in thyroid cancer has not been investigated yet.…”
Section: Introductionmentioning
confidence: 94%
“…More recently, it has been shown that vitamin C at pharmacologic plasma concentrations acquired intravenously can selectively kill the tumor cells but had little cytotoxic effect on normal cells; and these effect was mainly through a reactive oxygen species (ROS) dependent way [ 16 18 ]. These findings have inspired other studies to provide new insights into the function of combining therapy with vitamin C in treating different types of cancers [ 19 21 ]. Nevertheless, the function and the mechanism of combining therapy with vitamin C and PLX4032 in thyroid cancer has not been investigated yet.…”
Section: Introductionmentioning
confidence: 94%
“…Ascorbic acid has been used in combination with cisplatin as an adjunctive treatment for many cancers [95][96][97][98]. It has a wide range of pharmacological effects including anticancer, anti-inflammatory, antioxidant, anti-diabetic, wound healing, and anti-osteoporotic effects.…”
Section: Ascorbic Acid (Vitamin C) and Cancer Treatmentmentioning
confidence: 99%
“…In pre-clinical models, high-dose VitC is reported to enhance the effectivity of a wide variety of chemotherapeutics such as carboplatin [ 63 , 89 ], cisplatin [ 51 , 89 , 100 103 , 179 , 180 ], chlorambucil [ 181 ], 5-FU [ 88 , 89 , 182 ], gemcitabine [ 14 , 110 , 183 , 184 ] and temozolomide [ 16 , 54 ] in various cancer cell types, often in a synergistic manner or by enhancing treatment efficacy (Table 1 and Fig. 2 ).…”
Section: High-dose Vitc In Combination Treatmentsmentioning
confidence: 99%